Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Produk Di Toko Ramli Collection Gresik - Marsha, Tsabita Sufi; Aslamiyah, Suaibatul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The increasingly advanced development of the business world makes competition increasingly fierce, requiring enterpreneurs to analyze what factors influence purchasing decitions. This research aims to determine the influence of product quality, price and promotion on purchasing decisions at the Ramli Collection Gresik store. This research method is descriptive quantitative by obtaining primary data obtained directly from the source using a questionnaire. The population in this research are buyers who have made purchasing decisions about Ramli Collection Gresik products. The sample consisted of 144 respondents selected using the purposive sampling method. Data analysis uses research instrument tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The analytical tool used in this research is SPSS 23. The results of the research show, partially the Product Quality, Price and Promotion have a positive and significant effect on Purchasing Decisions at the Ramli Collection Gresik Store